Komodifikasi Agama dan Kepentingan Ekonomi Politik Media dalam Sinetron Para Pencari Tuhan - Latif Fianto; Fathul Qorib (Unitri Press, 2022)
Commodification is a process of transforming use value into exchange value. The soap opera The Search for God Volume 12 is the result of efforts to change the use value of religiosity into an exchange rate that can bring financial benefits. This study uses a critical perspective with an approach to the theory of media political economy. The concept of commodification of content offered by Mosco become the scalpel of this study. The data of this study is obtained from the main data source, namely the soap opera series of God Seekers Volume 12 which aired on SCTV. As for secondary data obtained from library studies or literature and internet. The result of the research shows that the soap opera of Para Pencari Tuhan (PPT) is nothing more than a commodification of aspects of spirituality or religion. Religious values that were originally viewed and used on the principle of use value were transformed into exchange values. Religion becomes a commodity in the midst of the industrialization of capitalist society. Media institutions have the power to determine a program will be used as new commodity on television screen. Every program produced by media institutions is a representative between the economic system and the political system. Abstrak Komodifikasi diartikan sebagai proses transformasi nilai guna menjadi nilai tukar. Sinetron Para Pencari Tuhan Jilid 12 adalah hasil upaya perubahan dari nilai guna relegiusitas ke dalam nilai tukar yang bisa mendatangkan keuntungan finansial. Nilai-nilai keagamaan dan ketuhanan dikomodifikasi menjadi tontontan yang layak jual. Kajian ini menggunakan perspektif kritis dengan pendekatan teori ekonomi politik media. Konsep komodifikasi isi yang ditawarkan Mosco menjadi pisau bedah kajian ini. Data kajian ini diperoleh dari sumber data utama, yaitu tayangan sinetron Para Pencari Tuhan Jilid 12 yang tayang di SCTV. Sedangkan untuk data sekundernya diperoleh dari studi kepustakaan atau literatur dan penelusuran internet. Hasil penelitian menunjukkan bahwa sinetron Para Pencari Tuhan (PPT) tidak lebih dari komodifikasi aspek spiritualitas atau agama. Nilai-nilai agama yang pada mulanya dipandang dan digunakan atas prinsip nilai guna ditransformasi menjadi nilai tukar. Agama menjadi komoditas di tengah industrialisasi masyarakat kapitalis. Lembaga media memiliki kekuatan (power) menentukan program apa saja yang akan dijadikan komoditas baru di layar kaca televisi. Setiap program yang diproduksi lembaga media adalah perwakinan antara sistem ekonomi dengan sistem politik.